2022
DOI: 10.1098/rsob.220124
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and cancer: biological mechanisms and clinical outcomes

Abstract: Evidence on aspirin and cancer comes from two main sources: (1) the effect of aspirin upon biological mechanisms in cancer, and (2) clinical studies of patients with cancer, some of whom take aspirin. A series of systematic literature searches identified published reports relevant to these two sources. The effects of aspirin upon biological mechanisms involved in cancer initiation and growth appear to generate reasonable expectations of effects upon the progress and mortality of cancer. Clinical evidence on as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Aspirin is involved in the proliferation and apoptosis of cancer cells through cyclooxygenase inhibition 29 . Furthermore, several signaling pathways are regulated in the antitumor process of aspirin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspirin is involved in the proliferation and apoptosis of cancer cells through cyclooxygenase inhibition 29 . Furthermore, several signaling pathways are regulated in the antitumor process of aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin is involved in the proliferation and apoptosis of cancer cells through cyclooxygenase inhibition. 29 Furthermore, several signaling pathways are regulated in the antitumor process of aspirin. The PI3K/AKT/mTOR pathway is a classic signaling pathway that regulates cell survival, proliferation, metabolism, and growth, which is a promising target for antitumor agents including aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) is frequently expressed in various tumors and plays a role not only in promoting tumor development but also elevating the resistance to chemotherapy and radiotherapy [ 111 ]. Aspirin exerts its anticancer effects via inhibition of COX, interference with proliferative pathways, cancer-related inflammation, and antiplatelet-driven pro-carcinogenic activity [ 112 ]. However, there is a risk of gastrointestinal and intracranial hemorrhage and other adverse effects associated with the long-term application of large amounts of aspirin.…”
Section: Novel Synthetic H 2 S Releasing Drugmentioning
confidence: 99%
“…To use anti-inflammatory drug aspirin or statin to repair ME degeneration-related tumor capsule disruptions. Previous studies have consistently demonstrated that aspirin or statin could significantly alter the chronic inflammation milieu of a variety of human cancers and prevent cancer progression 172 - 176 . Thus, the administration of aspirin or statin to individuals with focally disrupted MECL associated with significant infiltration of immune cells (as shown in Figure 10 ) may potentially reduce the extent of infiltrating immune cells.…”
Section: Specific Applications Of Mecl In Detection and Interventions...mentioning
confidence: 99%